Influence of social media food advertisement factors on consumers' purchase intention in Seri Kembangan, Selangor - Zainal Badari, Shamsul Azahari; Kei, Goh Mei; Goh, Mei Kei (Human Resource Management Academic Research Society, 2022)
Online shopping has become a new normal in Malaysia during the COVID-19 pandemic. More people tend to purchase food and groceries through social media and shopping online platforms. This study aimed to identify the influence of social media food advertisements factors on consumers’ purchase intention in Seri Kembangan, Selangor. The study was conducted in Seri Kembangan, Selangor with 200 respondents chosen by convenience sampling. Data collection has been done through an online platform. The results showed that age, household income, household size, and education level influenced consumers' purchase intention towards food advertisements on social media. Marketing factors such as price and quality perception were not significantly related to the purchase intention of consumers (p>0.05), while convenience perception was significantly related to consumers’ purchase intention (P<0.05) when it comes to food advertisements on social media. In conclusion, convenience perception is the only marketing factor that influences the purchase intention of consumers after viewing food advertisements on social media. Thus, this study can create awareness among consumers on the factors that influence food product purchasing and help marketers/food sellers by understanding the factors of food advertisements towards consumer purchase intention.